2009
DOI: 10.1590/s0103-73312009000300008
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação de competências de médicos e enfermeiros das Equipes de Saúde da Família da Região Norte do Brasil

Abstract: Trata-se de um estudo quantitativo, realizado com base na análise de questionários aplicados a médicos e enfermeiros dos Estados do Maranhão, Tocantins, Pará e Amapá, no ano de 2006. A pesquisa é parte integrante do Projeto de Expansão do Programa de Saúde da Família (PROESF), subsidiado pela Fundação Cesgranrio. Foram respondidos 346 questionários, sendo 160 por médicos e 186 por enfermeiros. Dentre os resultados encontrados, está o fato de que médicos e enfermeiros que trabalham na Saúde da Família da Região… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
3

Year Published

2011
2011
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 0 publications
0
6
0
3
Order By: Relevance
“…Of the 20 nurses interviewed in this study, most were females (19), twelve were within the 22 to 30 year age bracket and the others (8) fell within the 31 to 45 year age bracket. Of the total, twelve were married, six were single, one was in a consensual relationship and one was divorced.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…Of the 20 nurses interviewed in this study, most were females (19), twelve were within the 22 to 30 year age bracket and the others (8) fell within the 31 to 45 year age bracket. Of the total, twelve were married, six were single, one was in a consensual relationship and one was divorced.…”
Section: Resultsmentioning
confidence: 92%
“…Most subjects (19) had a lato sensu (specialization) graduate degree within several distinct areas, predominantly public health (12). When asked about the approach to health education in the graduate degree program, most (15) answered that health education was covered in the program, while four stated that it was not approached during the course.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of the professional demonstrated the knowledge that syphilis in pregnancy is considered a notifiable disease (82.2%), however, few of them adhered to the notification process, 30 considering that in Fortaleza more cases of congenital syphilis were reported than cases of syphilis in pregnant women in the years 2005-2009. This study involved FHS physicians and nurses, the professionals responsible for the diagnosis, treatment and monitoring of pregnant women with positive VDRL test results. It is worth mentioning the importance of ongoing education programs as a key factor for the development of healthcare practices based on scientific principles, 31 considering that more than half of these professionals had never undergone training related to syphilis. Training programs should develop attractive methodological strategies, as a study in the city of Duque de Caxias-RJ showed that FHS professionals did not feel motivated to participate in training, alleging that these programs did not add to the professional experience and that they were eminently theoretical.…”
Section: Discussionmentioning
confidence: 99%
“…Somente após a implantação do sistema de educação continuada houve uma melhora significativa no nível de conhecimento dos enfermeiros (26) . É importante destacar que um programa de educação permanente é indispensável para o desenvolvimento de uma prática baseada nos princípios científicos (27) . Contudo, os programas de treinamento devem desenvolver estratégias metodológicas atraentes, pois estudo anterior mostrou que os profissionais da ESF não se sentem motivados em participar dos treinamentos e relatam que não acrescentam nada à sua prática profissional e que os mesmos são predominantemente teóricos (28) .…”
Section: São Fases Da Sífilis Recenteunclassified